Pattern Recognition, Machine Intelligence and Biometrics 2011
DOI: 10.1007/978-3-642-22407-2_25
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Multimodal Biometric System—Rank Level Fusion

Abstract: Biometric identification referes to idetifying an individual based on his or her physilogical or beavioral characteristics. The use of more than one biometric identfiers in a biometric system, called the multimodal biometric system, increases the overall system accuracy and hence increase security, as well as reduce the enrollment problems. An effective and appropriate fusion strategy is needed to integrate different biometric information in such multimodal systems. This chapter provides an in-depth overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…For example, two persons may have the similar signature patterns, in which case, the signature verification system will produce large FAR for that system. Addition of face recognition system with the signature verification system may solve the problem and reduce the FAR [9]. Experiments have shown that the accuracy of multimodality can reach near 100% in identification.…”
Section: Multi-biometrics As a Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, two persons may have the similar signature patterns, in which case, the signature verification system will produce large FAR for that system. Addition of face recognition system with the signature verification system may solve the problem and reduce the FAR [9]. Experiments have shown that the accuracy of multimodality can reach near 100% in identification.…”
Section: Multi-biometrics As a Solutionmentioning
confidence: 99%
“…It prevents from stolen the templates of biometric system as at the time it stores the two characteristics of biometric system in the database [25]. For example, it would be more challenge for attacker to spoof many different biometric identifiers [9]. Further, when two or more modalities are used for authentication, it leads to become not easy to spoof the biometric system.…”
Section: Multi-biometrics As a Solutionmentioning
confidence: 99%
See 3 more Smart Citations